WhatsApp Marketing Strategy in Building Brand Awareness of Multi-Brand Muslim Fashion Products - Wasilatul Maufiroh; Moh. Idil Ghufron (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
WhatsApp, as a messaging app, is used by the Ely Collection store to send product promotion messages. This study aims to analyze the marketing method used by Ely Collection through the WhatsApp channel to build multi-brand Muslim fashion products in Pajarakan. The background of this research is the increasingly fierce competition in the Muslim fashion industry and the shift from conventional to digital marketing, especially among micro businesses that rely on direct consumer communication. This study uses a qualitative case study approach. Data was obtained through in-depth interviews, observations, and documentation, then analyzed using qualitative descriptive techniques. The results of the study show that WhatsApp is the primary medium for promotion, communication, and transactions, with users using status, catalog, and direct message features. This strategy can increase interaction and closeness with consumers and encourage customer loyalty. However, marketing effectiveness remains suboptimal due to obstacles such as inconsistent promotions, low sales conversion rates, and weak brand awareness stemming from multi-brand business models. This study concludes that WhatsApp has an important role in supporting relationship-based digital marketing in local Muslim fashion businesses. Strategic optimization, planned and consistent, is necessary to strengthen brand identity and improve sales performance.